The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jgh.13787
|View full text |Cite
|
Sign up to set email alerts
|

Repeated water avoidance stress induces visceral hypersensitivity: Role of interleukin‐1, interleukin‐6, and peripheral corticotropin‐releasing factor

Abstract: Repeated WAS for three consecutive days induced visceral allodynia, which was mediated through mast cells, IL-1, and IL-6 pathways. Inhibition of peripheral CRF signaling prevented but did not reverse this response, suggesting that peripheral CRF may be an essential trigger but may not contribute to the maintenance of repeated WAS-induced visceral allodynia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 43 publications
4
44
0
Order By: Relevance
“…As described before, LPS‐, repeated WAS‐, or CRF‐induced visceral allodynia and colonic hyperpermeability are considered to well simulate the pathophysiology of IBS, and we have previously demonstrated that CRF, TLR4, and proinflammatory cytokine signaling mediated these visceral changes …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As described before, LPS‐, repeated WAS‐, or CRF‐induced visceral allodynia and colonic hyperpermeability are considered to well simulate the pathophysiology of IBS, and we have previously demonstrated that CRF, TLR4, and proinflammatory cytokine signaling mediated these visceral changes …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, NO inhibits the expression of proinflammatory cytokine genes in various immune cells and suppresses IL‐1β release from macrophages . Incidentally, the chemical mediators including cytokines released by degranulation of mast cells are known to contribute to stress‐induced visceral hypersensitivity and gut hyperpermeability, and NO inhibits the degranulation to improve gut permeability . Thus, losartan may inhibit proinflammatory cytokine signaling by facilitating NO production to improve visceral changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Previous studies have demonstrated that stress increased CRF expression both in the brain and the intestine, 25,26 and CRF receptor antagonism both in the brain and in the periphery reversed visceral hypersensitivity induced by stress. 13,27 Another study examining the role of DNA methylation in visceral hypersensitivity showed that chronic water avoidance stress induced DNA methylation of the GR promoter and reduced its mRNA and protein expression in the dorsal root ganglia neurons innervating the pelvic viscera. 19 Chronic water avoidance stress also induced DNA methylation of the antinociceptive cannabinoid receptor 1 promoter and downregulated its expression, which may contribute to stress-induced visceral pain.…”
Section: Dna Methylationmentioning
confidence: 99%